Gas permeability of bread - Desyk, Mykola; Kozak, Oleksandr; Telychkun, Volodymyr; Nazarenko, Ivanna (My University, 2020)
The article presents the results of the study of the permeability of the crust and the central layers of bread products on the gases formed and transported from the workpiece to the environment by vacuum cooling. The scheme of experimental installation and a technique of research of permeability of layers of bread are offered. The influence of temperature and humidity of samples on the value of permeability was investigated. The values of the permeability of the bread crust to gases in different areas of the workpiece surface were found. The specific flow rates of gas through the surface of the products during vacuum cooling are found. The obtained results can be used to determine the modes of creating a vacuum in which the integrity of the samples is ensured

У статті наведено результати дослідження проникності кірки та центральних шарів хлібних виробів на гази, що утворюються та транспортуються із заготовки в навколишнє середовище шляхом вакуумного охолодження. Запропоновано схему експериментальної установки та методику дослідження проникності пластів хліба. Досліджено вплив температури та вологості зразків на величину проникності. Знайдено значення газопроникності скоринки хліба в різних ділянках поверхні заготовки. Знайдено питомі витрати газу через поверхню виробів під час вакуумного охолодження. Отримані результати можуть бути використані для визначення режимів створення вакууму, при якому забезпечується цілісність зразків
Keywords: gas permeability; випікання хліба; vacuum cooling; кафедра машин і апаратів харчових та фармацевтичних виробництв; газопроникність скоринки хліба; випікання хліба; вакуум-випарне охолодження